Total quality management in municipalities of the Klaipeda region - Burkšienė, Valentina (Socialiniai tyrimai, 2014)
The modern world obliges us to develop sustainably. Regions need to turn to sustainability by using all the available tools. Many authors emphasize total quality management (TQM) as a very important tool for the sustainable functioning of the public sector. But analyses show that public organizations are not keen to introduce TQM.This paper reveals the TQM spectrum in Klaipeda county (region) municipalities. Research disclosed that municipalities are not willing to implement TQM if it is not imperative. The paper argues that improving managerialism and common understanding can increase the willingness for TQM.
Keywords: total quality management; quality of public administration; public sector; sustainable development